The Role of Brand Image in Mediating the Effect of Brand Ambassador on Purchase Decision of Somethinc Products in Denpasar City - Sri Gandari, Ni Nyoman Mirah; Seminari, Ni Ketut (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to examine how the brand image of Somethinc products influences consumers' decisions to buy. Purposive sampling was used in this study, which had 120 respondents and was conducted in Denpasar. Questionnaires were distributed in order to collect data. Path analysis and the Sobel test were then used for analysis. According to the findings, brand ambassadors have a positive and significant impact on decisions about what to buy, and brand image also has a positive and significant impact on decisions about what to buy. Brand image also partially mediates the influence of brand ambassadors on decisions about what to buy. The research's consequences can serve as a reference and reinforce earlier findings.